Classical dynamics a contemporary approach - Jose, Jorge V. (Jorge Valenzuela) 1949-; Saletan, Eugene J. (Eugene Jerome) (Cambridge, England Cambridge University Press, 1998)
"Recent advances in the study of dynamical systems have revolutionized the way that classical mechanics is taught and understood. Classical Dynamics: A Contemporary Approach is a new and comprehensive textbook that provides a complete description of this fundamental branch of physics." "It will be an ideal textbook for graduate students of physics, applied mathematics, theoretical chemistry, and engineering, and will also serve as a useful reference for researchers in these fields"--Jacket.
Fundamentals of mechanics -- Lagrangian formulation of mechanics -- Topics in Lagrangian dynamics -- Scattering and linear oscillations -- Hamiltonian formulation of mechanics -- Topics in Hamiltonian dynamics -- Nonlinear dynamics -- Virigid bodies -- Continuum dynamics.
Includes bibliographical references (pages 657-662) and index.
Keywords: Mechanics, Analytic